Sistem Monitoring dan Kontroling Irigasi Pekarangan Bunga Berbasis Internet of Things (IoT) - Usman, Iqbal Faturachman; Hulukati, Stefan Adriansyah; Humena, Steven (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 3 (2025): JELIKU Volume 13 No 3, February 2025DO - 10.24843/JLK.2025.v13.i03.p11, 2025)
This study examines the challenges faced by farmers in Gorontalo in managing efficient irrigation water usage, especially due to weather uncertainties, climate change, and less optimal traditional irrigation methods. The purpose of this research is to design and develop an Internet of Things (IoT)-based monitoring and control system for irrigation to enhance water efficiency and productivity in flower gardens. The method involves implementing advanced sensors connected to a smartphone application, allowing real-time monitoring and automatic water flow adjustment based on specific plant needs and environmental conditions. The results show that the IoT system can gradually increase soil moisture from 1% to 70% within 10 minutes, indicating reduced water waste and increased irrigation efficiency. Additionally, the system enables real-time light control via WhatsApp, with data updating in real-time on a Spreadsheet to fulfill data requirements. The conclusion of this study is that IoT technology can provide a significant positive impact on the sustainability and productivity of the flower garden sector in Gorontalo, while also offering farmers convenience and flexibility in managing their irrigation